Synthesis, Characterization and Anti-Trypanosoma Cruzi Evaluation of Ferrocenyl and Cyrhetrenyl Imines Derived from 5-Nitrofurane - Godoy-Gonzalez, F; Godoy-Gonzalez, F (2011)
Sin Editorial Disponible